Maternal Health Seeking Behavior from a Sociocultural Perspective: A Qualitative Ethnographic Study - Arfiah Arfiah; Nurdin Rahman; Andi Mascundra Amir (Borneo Scientific Publishing, 2026)
Maternal healthcare behavior is shaped by biomedical, sociocultural, familial, and traditional factors. However, despite improvements in maternal health programs in Indonesia, limited evidence exists on how sociocultural processes influence maternal healthcare decision-making among indigenous communities. This study aimed to explore the sociocultural influences on maternal healthcare behavior among the Kaili Indigenous community in Loru Village, Central Sulawesi, Indonesia. A qualitative ethnographic study was conducted in Loru Village, Sigi Biromaru District, Central Sulawesi, Indonesia, between January and June 2025, involving seven participants selected through purposive sampling. Data were collected through in-depth semi-structured interviews, participant observation, document review, and triangulation interviews and analyzed using thematic analysis. The findings demonstrated that maternal healthcare behavior was strongly influenced by collective family decision-making, sociocultural values, customary authority, and traditional beliefs. Furthermore, culturally responsive communication by midwives and collaboration with traditional birth attendants increased community acceptance of formal maternal healthcare services while respecting local cultural practices. These findings indicate that maternal healthcare behavior within the Kaili Indigenous community is a socially and culturally embedded process rather than an individual health decision. They further highlight the potential of culturally responsive maternal healthcare strategies that actively engage families, community leaders, and traditional birth attendants to improve maternal healthcare utilization and strengthen culturally appropriate service delivery in indigenous settings. Further research involving multiple indigenous communities, larger participant groups, and comparative ethnographic designs is warranted to confirm the transferability of these findings and broaden understanding of sociocultural influences on maternal healthcare behavior across diverse cultural contexts.